Sistem Aplikasi Pada Multi Channel Power Socket Untuk Pengukuran Daya Pada Kompleks Ruko Dan Apartemen - Yoshua Dennish Kurniawan; Resmana Lim; Agustinus Noertjahyana (Universitas Kristen Petra, 2022)
Along with solid human activity, especially at work time. Sometimes forget to turn off or turn on the electronic device so that the cost of electricity is vulnerable to cost overruns. This is coupled with the possibility of damage to components that make energy efficiency less. If we don't measure the use of energy on electronic devices, then we can't detect that there are problems with electronic devices. This problem will be resolved by the author by utilizing the internet network of an application and a tool for monitoring energy consumption and controlling the life of the installed load. The results of testing this tool in energy monitoring have a margin of success reaching 95.72%.